Composition and Antioxidant Activity of Phenolic Compounds in Fruit of the Genus Rosa L. - Mindaugas Liaudanskas; Irena Noreikienė; Kristina Zymonė; Rugilė Juodytė; Vaidotas Žvikas; Valdimaras Janulis (MDPI AG, 2021)
We investigated the qualitative and quantitative composition of phenolic compounds in the fruit of Rosa L. cultivars grown in Lithuania. The highest total content of phenolic compounds (50.13 ± 4.17 mg GAE/g, p < 0.05) was determined in fruit samples of Rosa pimpinellifolia L. cultivar "Single Cherry". The highest levels of hydroxycinnamic acid derivatives were determined in fruit samples of Rosa rugosa Thunb. cultivars "Dart's Defender" and "Adam Chodun". The highest flavonoid content was determined in fruit samples of Rosa multiflora Thunb. cultivar "Nana" and R. multiflora species. The strongest antioxidant activity evaluated by applying DPPH and FRAP assays was determined in fruit extracts of R. pimpinellifolia cultivar "Single Cherry" and R. rugosa cultivar "Adam Chodun". Qualitative and quantitative analysis of phenolic compounds in Rosa L. fruit was performed by applying UHPLC. The following phenolic compounds were identified in fruit samples: caffeic acid, chlorogenic acid, quercetin, quercitrin, (+)-catechin, (−)-epicatechin, (−)-epicatechin gallate, rutin, phloridzin, and kaempferol-3-O-glycoside. A strong correlation was determined between the total amount of phenolic compounds determined in extracts of the fruit samples of Rosa L. cultivars and the radical scavenging and reducing activity of their extracts in vitro (R = 0.767 and 0.727, respectively, p < 0.05).